Modeling the relationship between the main emulsion components and stability, viscosity, fluid behavior, ?-potential, and electrophoretic mobility of orange beverage emulsion using response surface methodology - Mirhosseini H.; Tan C.P.; Hamid N.S.A.; Yusof S. (2024)
Indexed by WOS/ Scopus